Target Tracking in Mobile Robot under Uncertain Environment using Fuzzy Logic Controller - Ade Silvia Handayani; Tresna Dewi; Nyayu Latifah Husni; Siti Nurmaini; Irsyadi Yani (IAES Indonesia Section, 2017)
This paper discusses a design of fuzzy logic algorithm in a robot. This algorithm is useful for the robot in seeking and reaching the target. The robot is also accomplished with an ability to avoid obstacles. Although the fuzzy rule that is embedded to the robot is very simple, it gives a good result in target seeking and obstacles avoiding task. The originality of this research is an approach to the rules that can simplify the task by creating faster track for the robot in uncertain environment.